Assessing individual-level needle and syringe coverage parameters and the measurement of coverage in Melbourne, Australia: methods and impacts. (21st December 2017) - O'Keefe, D; Scott, N; Aitken, C; Dietze, P
Abstract: Background: To assess the structure of individual-level needle and syringe coverage measurement formula, and to estimate the impact of coverage-related behaviours/parameters (instances of syringe acquisition, total syringes acquired, peer-to-peer syringe distribution, injecting frequency) on overall coverage. Methods: Data are drawn from the Melbourne (Australia) injecting drug user cohort study, 2010–16. Data from 518 participants were analysed. We used correlations to explore the relationships between coverage parameters; pooled multiple–linear regression to estimate the effect of each parameter on coverage over time; and exploratory factor analysis to assess the relevance of each parameter within the coverage formula. Results: A 1-unit increase in injecting frequency over time reduced coverage by 10.93 percentage points, almost twice as much as other coverage parameters. Factor analysis results indicated potential improvements to coverage formula structure. Conclusions: Our results suggest that reducing injecting frequency amongst people who inject drugs has the largest improvement in coverage levels, indicating harm reduction services should prioritize it. We also demonstrate that coverage measurement has been inconsistent to date. We sought to refine the method to assist in generating comparable research.